2019
DOI: 10.1101/2019.12.16.876086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A spectral jamming avoidance response does not help bats deal with jamming

Abstract: 6For decades, researchers have speculated how echolocating bats deal with acoustic 7 interference created by conspecifics when flying in aggregations. It is thus surprising that 8 there has been no attempt to quantify what are the chances of being jammed, or how such 9 jamming would affect a bat's hunting. To test this, we developed a computer model, 10 simulating numerous bats foraging in proximity. We used a comprehensive sensorimotor 11 model of a hunting bat, taking into consideration the physics of sound … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Since frequency adjustments occur frequently and under various conditions, an adaptation that purely depends on a JAR may not be sufficient to orient collision-free in the presence of signal interferers. This hypothesis gains support by recent simulations that have tested for the effectiveness frequency adjustments when navigating in noisy environments (Mazar and Yovel, 2019). Note that some studies reported that bats do not shift their frequency in response to acoustic interference (Götze et al, 2016) or that the frequency shifts are correlated with the object's distance rather with the presence of an acoustic interferer (Cvikel et al, 2015).…”
Section: Coping With Signal Interferencementioning
confidence: 61%
“…Since frequency adjustments occur frequently and under various conditions, an adaptation that purely depends on a JAR may not be sufficient to orient collision-free in the presence of signal interferers. This hypothesis gains support by recent simulations that have tested for the effectiveness frequency adjustments when navigating in noisy environments (Mazar and Yovel, 2019). Note that some studies reported that bats do not shift their frequency in response to acoustic interference (Götze et al, 2016) or that the frequency shifts are correlated with the object's distance rather with the presence of an acoustic interferer (Cvikel et al, 2015).…”
Section: Coping With Signal Interferencementioning
confidence: 61%